Great Ajax - Griffiths, David 1969- (O'Reilly Media, 2010)
"Great Ajax: Level 1 will teach you the basics of programming asynchronous web applications. You'll begin with the simplest interactions, using XmlHttpRequest. But before long, you'll be building chat servers, working with databases and remote services, and doing it all without the user waiting around or clicking Submit buttons. You'll take on XML and JSON, and use both data formats to make your pages and web apps responsive and user-friendly. Throughout the course, you'll learn how to think about web apps in a totally different manner. Beyond the syntax of Ajax requests, you'll look into lazy loading, interacting with remote servers, and building apps that respond to user expectations, not just their clicks and typing. You'll also get a handle on the sorts of HTML and CSS considerations you'll need to master to really take your web apps to the next level."--Resource description page.